Respuesta :

Just flip the signs of co-ordinates by using formula y=>-y

  • Make sure to do this with y only as it has been reflected to y axis

[tex]\\ \ast\bull\rm\longmapsto Z(-5,-4)\implies Z'=(-5,-(-4))\implies Z'=(-5,4)[/tex]

[tex]\\ \ast\bull\rm\longmapsto Y(-3,-4)\implies Y'=(-3,-(-4))\implies Y'=(-3,4)[/tex]

[tex]\\ \ast\bull\rm\longmapsto X(-5,-1)\implies X'=(-5,-(-1))\implies X'=(-5,1)[/tex]

Answer:

• Reflection about the x-axis, consider a point A

[tex]{ \tt{A(x,y) \: \dashrightarrow \:A {}^{i} ( - x, \: y) }}[/tex]

• Therefire, coordinates of X'

[tex] \dashrightarrow \: { \boxed{ \tt{X( - 5, \: - 1) = X'(5, \: - 1)}}}[/tex]